Analisis Kebutuhan E-Komik Interaktif Berbasis Permainan Tradisional Tungkupan Sebagai Media Literasi Anak Usia Dini - Rosa, Evira; Sumarni, Sri; Syarifuddin (UNIB Press, 2025)
This study aims to develop and analyze the need for interactive e-comics based on the traditional game of Tungkupan as a learning medium for early childhood in Palembang. The research method used is descriptive exploratory with a mixed-methods approach, which includes a quantitative survey of 141 kindergarten teachers and qualitative interviews with 30 kindergarten children. The results of the study indicate that the development of e-comics based on local culture can increase learning interest, strengthen cultural identity, and support the development of children's digital literacy from an early age. The main obstacles faced are limited access to devices and internet connections, as well as the need for attractive and relevant media design. E-comics that feature the traditional game of Tungkupan not only serve as an educational medium but also as a tool for preserving local culture, in line with the principles of the Merdeka Curriculum and culture-based pedagogy. With a collaborative design that considers technological aspects and local values, this innovation is expected to enrich children's learning experiences and preserve cultural heritage in the digital age.